(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article deals with various aspects of the impact of information technology on social and political processes of modern society. The basis for the understanding of such influence was the theory of post-industrialism and the concept of a simulation of reality. Based on these concepts to draw conclusions about the virtualization of society as a whole, and political processes in particular.Reveals the possible positive and negative aspects of this transformation of mass consciousness.